Alleviation of symptoms and paradoxical brain perfusion shift in oral cenesthopathy: A retrospective neuroimaging study - Umezaki, Yojiro; Motomura, Haruhiko; Nagamachi, Shigeki; Toyofuku, Akira; Tu, Trang Thi Huyen; Naito, Toru (Frontiers in Psychiatry, 2025)
IntroductionOral cenesthopathy is characterized by abnormal, distressing oral sensations without identifiable physiological or pathological causes. Right side predominant regional cerebral blood flow (rCBF) asymmetry in the broad brain area is suggested as pathophysiology of oral cenesthopathy. Coping behaviors, which provide temporary symptom relief, are sometimes employed by patients, but their effect on brain function is unclear. This study aims to examine changes in rCBF associated with coping behaviors.MethodsSeven patients with oral cenesthopathy were included in this study. Each patient underwent two single photon emission computed tomography (SPECT) scans: one during the state of discomfort (at steady state) and another after performing coping behaviors. SPECT data were analyzed using three-dimensional stereotactic regions of interest template, and Fine stereotactic regions of interest template.ResultsAt the steady state, right-side rCBF predominated in several brain regions, including the temporal lobe, without significant difference. During coping behaviors, this right-sided rCBF asymmetry was amplified, and showed significant differences, including the fusiform, lingual and parahippocampal gyri. These regions, associated with visual processing, suggest that oral cenesthopathy may involve more than just somatosensory dysfunction.ConclusionCoping behaviors in oral cenesthopathy were associated with amplified right-sided rCBF asymmetry. This finding challenges the expectation that symptom alleviation would reduce rCBF asymmetry. It may suggest that the coping behavior of the patients with oral cenesthopathy is potentially amplifying asymmetry especially in the higher visual processing to adapt to their symptoms.